2011
DOI: 10.1111/j.1468-3148.2011.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Actual Levels and Patterns of Physical Activity/Inactivity of Adults with Intellectual Disabilities

Abstract: Background Lack of regular physical activity is a significant risk to health. The aim of this study was to objectively measure the levels and patterns of activity of adults with intellectual disabilities, to inform the design of studies aimed at increasing activity and health in this population. Materials and Methods Interviews were conducted with 62 community-based adults with mild to moderate intellectual disabilities at the start and at the end of a 7-day period of physical activity ⁄ inactivity measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 21 publications
1
42
0
Order By: Relevance
“…Our data suggests that a majority of individuals with ID do not exercise frequently enough to achieve health benefits: less than one third of our sample (27%) reported engaging in regular, consistent physical activity. Furthermore, nearly half of our sample (42%) reported never exercising, similar to findings from other studies (Bodde et al, 2013;Finlayson et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data suggests that a majority of individuals with ID do not exercise frequently enough to achieve health benefits: less than one third of our sample (27%) reported engaging in regular, consistent physical activity. Furthermore, nearly half of our sample (42%) reported never exercising, similar to findings from other studies (Bodde et al, 2013;Finlayson et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Released in 2008, The Physical Activity Guidelines for Americans recommends that Americans engage in at least 30 min per day of moderate-to-vigorous physical activity (MVPA) 5 days per week (U.S. Department of Health and Human Services, 2008). Although 47% of adult Americans satisfied this recommendation in 2010 (U.S. Department of Health and Human Services, 2013), only 15% of individuals with ID did so (Finlayson, Turner, & Granat, 2011). Furthermore, Bodde and colleagues (2013) suggested that individuals with ID accumulate, on average, only 7.73 min of MVPA per day.…”
mentioning
confidence: 96%
“…20-23;30-34 Studies differed in defined wear time and specific days of the week included. The two inclinometer studies had a seven-day wear time, with a wear time of at least five days being required by Finlayson et al 29 All nine studies using accelerometers invited participants to wear the accelerometers for seven days. However, the minimum wear time required for inclusion in the analysis varied across the eight studies.…”
Section: Methods Of Measurementmentioning
confidence: 99%
“…It is also an activity that can be carried out with very sedentary or inactive populations: therefore it can be an appropriate exercise intervention for adults with intellectual disabilities. A small body of work has focussed specifically on measuring walking behaviours of adults with intellectual disabilities [16-22]. Generally, studies have used pedometers or accelerometers to measure steps walked per day.…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that adults with intellectual disabilities walk between 6481 and 11,101 steps per day [17-20]. It has been suggested that 10 minutes of brisk walking equates to roughly 1,000 steps for the general population and 800 steps for adults with intellectual disabilities [22,23]. Therefore, participants in these studies appear to be doing significantly more walking than those who were included in the population based study.…”
Section: Introductionmentioning
confidence: 99%